Antimicrobial activity of four medicinal plants widely used in Persian folk medicine - A. Hamedi; K. Zomorodian; F. Safari (Iranian Society of Pharmacognosy, 2015)
Background and objectives: Commiphora habessinica (O.Berg) Engl. (Burseraceae), Boswellia sacra Flueck (Burseraceae), Phoenix dactylifera L. (Arecaceae), and Doronicum glaciale (Wulfen) Nyman (Asteraceae) are of ethnomedicinal importance in Persian folk medicine and are widely used to treat infectious diseases. The aim of the present study was to investigate the antimicrobial properties of these herbal medicines to prevent misadministration. Methods: Antifungal and antibacterial (Gram-positive and Gram-negative) activities of the petroleum ether, dichloromethane and ethanol fractions obtained from oleo-gum-resin of C. habessinica and B. sacra, spathe of P. dactylifera and roots of D. glaciale were evaluated against standard species and clinical antibiotic resistant isolates using broth microdilution method. The fractions were tested at concentrations of 0.5 to 256 µg/mL.Results: The petroleum ether fraction of C. habessinica oleo-gum-resin exhibited the most anti-Candida activity with MIC50 of 0.5-16 µg/mL. The growth of C. glabrata and C. tropicalis was inhibited by the ethanol fraction of C. habessinica oleo-gum-resin with MIC50 of 1-16 μg/mL. C. glabrata was the most susceptible species. Among the tested fractions, only the petroleum ether fraction of C. habessinica oleo-gum-resin had an inhibitory effect on Aspergillus spp. with a MIC50 of 8-32 µg/mL. None of the fractions exhibited antimicrobial activity against the Gram-positive and Gram-negative bacteria at concentrations of 0.5 to 256 µg/mL. Conclusions: The sensitivity of fungi and bacteria to natural antimicrobials varies widely within species and it is essential to consider the sensitivity of the strains to prevent resistance.